Phytochemical Analysis and Cholinesterase Inhibitory and Antioxidant Activities of Enhydra fluctuans Relevant in the Management of Alzheimer’s Disease - Simin Shabnam Lopa; Md. Yusuf Al-Amin; Md. Kamrul Hasan; Md. Salim Ahammed; KM Monirul Islam; A. H. M. Khurshid Alam; Toshihisa Tanaka; Md. Golam Sadik (International Journal of Food Science)
Enhydra fluctuans, a popular vegetable in Bangladesh, is used in folk medicine to treat diseases of the nervous system. The objective of this study was to investigate the phytochemical profile and cholinesterase inhibitory and antioxidant potential of the extracts of E. fluctuans. Among the four tested extracts, the chloroform extract was found to exert the highest inhibition against both the acetylcholinesterase and butyrylcholinesterase enzymes with the IC50 (concentration required for 50% inhibition) values of 83.90 μg/mL and 48.14 μg/mL, respectively. Likewise, the chloroform extract showed the highest radical scavenging activity and reducing power. In DPPH radical scavenging assay, the IC50 value was found to be 113.27 μg/mL, and in reducing power assay, the absorbance was found to be 1.916 at a concentration of 50 μg/mL. Phytochemical analyses revealed that the chloroform extract contained 19.16 mg gallic acid equivalent (GAE)/g extract of phenolics and 41.84 mg catechin equivalent (CE)/g extract of flavonoids, which appeared to be the highest among the extracts. A significant correlation was observed between phenolic content and butyrylcholinesterase inhibition and antioxidant activity, while a moderate correlation was seen between flavonoid content and cholinesterase inhibition and antioxidant activity. These findings suggest that E. fluctuans is a natural source of cholinesterase inhibitors and antioxidants, which could be utilized as functional foods for Alzheimer’s disease management.